Pengaruh Social Media Marketing Terhadap Keputusan Pembelian dengan Kepuasan Konsumen Sebagai Variabel Intervening pada Rumah Tanda Tangan - Bagas Afriansyah Dewa; Muhammad Sandy Pratama; Willy Cahyadi; Cici Puspaningrum (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine the Influence of Social Media Marketing on Purchasing Decisions with Consumer Satisfaction as an Intervening Variable at Rumah Tandatangan. The analysis method used in this study is using an instrument test, namely validity and reliability tests. Classic assumption tests, namely normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, determination coefficient analysis (R2), hypothesis tests, namely T Test and Path Analysis. The results of the study indicate that Social Media Marketing Affects Consumer Satisfaction at Rumah Tandatangan, Social Media Marketing Affects Purchasing Decisions at Rumah Tandatangan, Consumer Satisfaction Does Not Affect Purchasing Decisions at Rumah Tandatangan, Social Media Marketing Does Not Affect Purchasing Decisions with Consumer Satisfaction as an Intervening Variable at Rumah Tandatangan.